Regional experience with Brachiaria: Sub-Saharan Africa - Ndikumana, J.; Leeuw, P.N. de (International Center for Tropical Agriculture, 1996)
In tropical Africa, the most common and most extensively evaluated Brachiaria species as cultivated pastures are B. brizantha, B. ruziziensis, B. decumbens, and B. mutica. In recent years, B. dictyoneura cv. Llanero, B. humidicola, and B. platynota have also received increased attention. The first four species produce high yields, show excellent response to fertilizer, are persistent, and remain green long into the dry season. Although, in Africa, data on nutritive value are incomplete and scattered, they indicate that forage from Brachiaria is highly palatable to stock, leading to high intake, whether fed fresh or grazed in situ. These species have also shown broad adaptation to different ecological zones. Although some may be drought-resistant, they perform best in the subhumid and humid zones where rainfall exceeds 800 mm and the growing season is more than 6 months. Low temperature depresses growth; therefore, Brachiaria in general, performs poorly at altitudes above 1,800 m. Further research is needed to place selected ecotypes of Brachiaria and other perennial forage species in the context of farming systems and develop integrated crop-livestock production systems for sub-Saharan Africa.